Ischemic Stroke and Serum CPK: A Review - Alam, SK Mahbub; Md Arifuzzaman, -; Rahman, Hafizur; Rahman, Hasan Zahidur; Islam, Md Rafiqul (Bangladesh Journal of Neuroscience, 2014)
Abstract not available Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 112-116